Nonlinear Analysis of Active Aperture Coupled Reflectarray Antenna Containing Varactor Diode - Aryanian, I.; Abdipour, A.; Moradi , G. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Radiation pattern of reflectarray antenna can be controlled using varactor diode in the antenna structure, but may cause nonlinear response. Thus, it is needed to design active reflectarray antenna considering nonlinear behavior of the unit cell. However, in the past papers, active element of varactor tuned reflectarray antenna is assumed linear, while in this paper, nonlinear analysis of active reflectarray antenna is explained and an active aperture coupled reflectarray unit cell containing two varactor diodes is analyzed. Harmonic balance method is used in analyzing active unit cell using nonlinear model of the diode. Therefore, this paper shows the significance of nonlinear analysis of active reflectarray antenna, and also the effect of nonlinear element in radiation pattern is presented. By the explained method, the impact of nonlinearities on performance of reflectarrays can be investigated. Furthermore, any active reflectarray cell having active device by any nonlinear model can be used in the analysis, and the impact of parameters of the model can be studied.